Kemampuan Berpikir Kreatif Siswa Menggunakan Model Pembelajaran Simas Eric Berbantu Media Canva Pada Materi Keanekaragaman Hayati - Milad Mardiyah; Milla Listiawati; Asrianty Mas’ud (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The ability to think creatively is one of the abilities needed in 21st century learning. However, based on the facts in the field, it can be seen that if the biology lesson is carried out, the teacher has not been oriented towa rds learning that can train students' creative thinking skills. The purpose of this study was to analyze students' creative thinking skills using the Simas Eric learning model assisted by Canva media on biodiversity material. The method used in this study is a quasi experiment method with a type of non-equivalent control group design using two classes, namely classes X-E and X-G and research subjects as many as 66 students. The instruments used in the from of descriptive  questions totaling 15 questions. Data analysis was carried out using Microsoft Excel. Data on students' creative thinking skills in the form of the average value of the experimental class pretest which is 50 and posttest 64, while the control class pretest average value is 52 and postest 59. The results of the hypothesis test showed that there was an effect of the Simas Eric learning model assisted by canva media on creative thinking skills on biodiversity material.